2007
DOI: 10.1002/mar.20186
|View full text |Cite
|
Sign up to set email alerts
|

Privacy attitudes and privacy‐related behavior

Abstract: A significant body of research has arisen over the last few decades describing the causes of observed incongruity between attitudes and behaviors. Recent work in the area of privacy has demonstrated this type of situation, in which people with negative attitudes toward the provision of personal information will disclose this very same information for no apparent benefit. However, little theoretical work has been developed to explain why this paradoxical anomaly exists. This paper suggests that attribution play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 51 publications
0
36
1
Order By: Relevance
“…A second limitation is that the outcome variable measures participants' acceptability of the different information disclosure scenarios. Although people's perception or intent is closely related with actual behavior [2], especially when both are measured in a specific context, studies have shown that users may behave in ways that seemingly contradict their stated personal information disclosure intentions [35]. However, since we cannot implement real-world scenarios to collect participants' actual behavioral response due to time and cost, this is the closest reaction that we can get.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second limitation is that the outcome variable measures participants' acceptability of the different information disclosure scenarios. Although people's perception or intent is closely related with actual behavior [2], especially when both are measured in a specific context, studies have shown that users may behave in ways that seemingly contradict their stated personal information disclosure intentions [35]. However, since we cannot implement real-world scenarios to collect participants' actual behavioral response due to time and cost, this is the closest reaction that we can get.…”
Section: Discussionmentioning
confidence: 99%
“…about accountability and identifiability) have opposite effects in individualist and collectivist cultures. This cultural variability of attitudinal effects may be yet another reason for the existence of the privacy paradox [35], i.e. the surprisingly weak link between privacy attitudes and behaviors.…”
Section: Implications For Privacy Research and Petmentioning
confidence: 99%
“…It is well known that attitudes do not always predict actual behavior [Ajzen 2001], and this also appears to be true in the realm of privacy attitudes and privacy-related behavior [Norberg and Horne 2007]. As quality of life technology applications are developed, studies of users in realworld settings that examine actual privacy-related behaviors will become necessary.…”
Section: -Multiple Regression Analyses Of Informational Privacy Attitmentioning
confidence: 98%
“…The product is likely to be seen as unique when a disclosure is unique but not when a disclosure is common (not unique). Attributional activities can influence attitudes (e.g., Norberg & Horne, 2007), and both inferences affect brand attitudes, as described in the columns on the left-hand side of Table 1 (below "no cognitive load").…”
Section: A Multistage Attribution Perspective Of Two-sided Message Prmentioning
confidence: 99%